Empirical Study on Migrating Data From Relational Databases To Object-Oriented Technology. (International Journal of Engineering and Computer Science, 2013)
Tremendous changes have been taking place in information technology for a few decades. Due to the rapid evolution in this area, the demand for innovation in this area is much higher than elsewhere. This requires large effort of companies to respond quickly to market conditions in order to organize work and conduct business more efficiently. In particular, companies have to reengineer existing form of new key technologies like WWW or E-Commerce. A typical scenario in many companies when applying a reengineer process is That on the one hand, a large body of data is captured in relational or even hierarchal or network databases, and on the other hand object oriented applications have to be developed. Thereby, a new object model is constructed which represents the current state of the company’s business processes. However, the new object model and the existing relational database’s model usually do not go well together. In other words, a large semantic gap between both models must be bridged. The approach proposed in this paper is database migration. Basically, this approach comprises two tasks. In the first task, the relational database schema is reengineered. The schema is transformed into a well designed and intuitively understandable object oriented schema, which the new applications can adapt. Afterwards, the data are (automatically) migrated into an object oriented DBMS. An algebra is proposed for a formal definition of data migration process. The schema transformation process is subdivided into three sequential phases. In the first phase, the relational schema is transformed (automatically) into an SOT schema. This initial SOT schema is then redesigned resulting in the adequate object oriented schema. Finally, in the third phase t resulting SOT schema is (again automatically) transformed into an object oriented schema according to the ODMG standard. The data migration process is generated automatically for each schema transformation phase. In order to implement schema transformation, the concept of transformation rule is proposed. The transformation rules define elementary restructuring operations within the SOT model. A basic set of transformation rules has been proposed which can be extended. Finally, a prototype has been implemented as a proof of concept.